2017
DOI: 10.1093/jxb/erx145
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent protein kinase OsCPK10 mediates both drought tolerance and blast disease resistance in rice plants

Abstract: OsCPK10 mediates drought tolerance and blast disease resistance in rice plants by enhancing their reactive oxygen species scavenging capacity and so reducing oxidative damage associated with both stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 75 publications
1
36
0
Order By: Relevance
“…But there were still a few BdCDPK genes which might execute their function continuously. Interestingly, it exhibited a similar expression pattern in the B. distachyon seedlings subjected to salt, drought and oxidative stresses, which was consisted with the previous reports that many CDPKs were involved in both salt and drought stresses, and they positively mediated tolerance to these stresses by protecting plants from reactive oxygen species (ROS) damage, with the uncontrolled generation of ROS being a common feature of these stresses [80,[89][90][91]. Notably, a set of genes (BdCDPK09, 10, 11, 12, 13, and 20) were up-regulated 0-12 h post treatment with NaCl and PEG, while they were up-regulated 12-24 h post treatment with heat stress, implying these BdCDPKs might play different roles in response to these stresses.…”
Section: Expression Profile Of Bdcdpk Genessupporting
confidence: 84%
“…But there were still a few BdCDPK genes which might execute their function continuously. Interestingly, it exhibited a similar expression pattern in the B. distachyon seedlings subjected to salt, drought and oxidative stresses, which was consisted with the previous reports that many CDPKs were involved in both salt and drought stresses, and they positively mediated tolerance to these stresses by protecting plants from reactive oxygen species (ROS) damage, with the uncontrolled generation of ROS being a common feature of these stresses [80,[89][90][91]. Notably, a set of genes (BdCDPK09, 10, 11, 12, 13, and 20) were up-regulated 0-12 h post treatment with NaCl and PEG, while they were up-regulated 12-24 h post treatment with heat stress, implying these BdCDPKs might play different roles in response to these stresses.…”
Section: Expression Profile Of Bdcdpk Genessupporting
confidence: 84%
“…To adapt to water-deficit conditions, plants regulate various cellular processes, including transcription, translation, and post-translational modification. Protein phosphorylation via plant kinases is a post-translational modification process, and it plays an important role in ABA signaling and the drought stress responses (Bundo and Coca, 2017;Yang et al, 2017). Several stress-related kinases have been identified and functionally characterized; nevertheless, the precise mechanisms by which plants respond to stress remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…One such annexin, OsANN1, functions as an ATPase with the ability to bind Ca 2+ and regulate the inflow and efflux of Ca 2+ ions. Through the interaction with OsCDPK10 , a protein kinase, OsANN1 confers abiotic stress tolerance via antioxidant accumulation [ 267 ]. Further, through yeast two-hybrid system analyses, it was demonstrated that OsANN1 interacts with OsCDPK24 and, therefore, regulates abiotic stress responses [ 268 ].…”
Section: Genes Regulating Ros Homeostasis In Abiotic Stressmentioning
confidence: 99%